Feasibility of Targeted Case-Finding of Polyendocrine Metabolic Ovarian Syndrome in the Workplace: A Pilot Cohort Study - Nicola Magnavita (International Journal of Environmental Research and Public Health, 2026)
Polyendocrine metabolic ovarian syndrome (PMOS) is the most common endocrine disorder in working women. Workplace screening could contribute to the early diagnosis and treatment of this chronic condition. Fertile women who participated in a 2022 health food promotion campaign and had suspected eating disorders, overweight/obesity, metabolic abnormalities, sleep problems, or mental health concerns were interviewed about PMOS symptoms during their in-office medical examination. Twenty-eight of the 1170 women examined had symptoms of suspected PMOS. By 2023, 21 of these diagnoses had been confirmed by specialists. The prevalence of newly diagnosed PMOS among the women of childbearing age was 2.7% (CI95% 1.7; 4.2). The confirmation rate of the clinical suspicion of PMOS was 75% (CI95% 55.1; 89.3). Female workers with newly identified PMOS had a significantly higher frequency of eating disorders than their pre-menopausal colleagues and higher body mass index values, higher glycemia, and higher cholesterol values. PMOS patients also had higher depression symptom scores than other workers of childbearing age. In conclusion, with a short interview during mandatory medical examinations, the occupational physician can make a significant contribution to the diagnosis of PMOS, thereby hopefully improving the quality of life of women and reducing damage to their health.